If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 2(x + -2) = -3 + x Reorder the terms: 1 + 2(-2 + x) = -3 + x 1 + (-2 * 2 + x * 2) = -3 + x 1 + (-4 + 2x) = -3 + x Combine like terms: 1 + -4 = -3 -3 + 2x = -3 + x Add '3' to each side of the equation. -3 + 3 + 2x = -3 + 3 + x Combine like terms: -3 + 3 = 0 0 + 2x = -3 + 3 + x 2x = -3 + 3 + x Combine like terms: -3 + 3 = 0 2x = 0 + x 2x = x Solving 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x 1x = x + -1x Combine like terms: x + -1x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 40+x=35 | | 6(x+20)=180 | | 4x-x+3=3x-5+8 | | 6x^2=10-28x | | F(x)=25+5x | | -7k+34=3k-2(8k-5) | | 4-8r=-4(5r-1) | | x^2-13.5+38=0 | | 3x-4[2x-5]=5 | | 7+.2X=5+.3 | | 12x+8y=500 | | 4(4x-2)=-104 | | 8+5x= | | -15-3r=-4(r+2) | | -740+500+-1000= | | -3(n-4)-(-7n-4)=72 | | 18-3[x+5]=24 | | 2(m+2)+m=19-(2m+3) | | 4(6+7m)=24+4m | | X^4-x^3-5x^2+4x+4=0 | | 4x-2=10+3x | | 12(x-3)-6=3x-3 | | 6x-54+5x-41=37 | | 9(3+5)=225 | | Cos*5x=1 | | mx+6=15m | | 5n=-0.3 | | 38-7b=1-3(4b+1) | | 775x=3.75+7 | | g^2+16g=41 | | 2x(x+6)=4x-12 | | 1x-5=x^2-5 |